Entrepreneurship education and ecosystem influence on students' entrepreneurial intentions - Tran, Anh Viet; Nguyen, Tram Huynh Mai; Nguyen, Trung Thanh; Tran, Hung Van (Journal of Asian Scientific Research, 2025)
This research examines how entrepreneurship education and the entrepreneurial environment of university students impact their entrepreneurial intentions in Vietnam, particularly regarding their perceived entrepreneurial will. Using a two-tiered research strategy, the study first employed an exploratory approach, followed by a survey involving 1,088 undergraduate students across different academic years from universities and colleges in Ho Chi Minh City and Hanoi. The results provide evidence that entrepreneurship education has both direct and indirect effects on students' entrepreneurial intentions, mediated by two crucial variables: the entrepreneurial ecosystem and perceived entrepreneurial desire. In particular, a robust business environment characterized by supportive policies, adequate infrastructure, and high-quality entrepreneurial services is essential in shaping students’ intentions to engage in entrepreneurship. This desire acts as a psychological trigger, transforming general knowledge into specific entrepreneurial intentions. The research demonstrates that perceived entrepreneurial intent is not solely a consequence of education and environment but also a vital element in the process of intention formation. The study offers recommendations for policies aimed at enhancing the quality, practical relevance, and workplace applicability of entrepreneurship education, as well as fostering the entrepreneurial ecosystem. These steps are critical for cultivating an innovative culture, enabling future entrepreneurs, and supporting Vietnam’s creative economy in sustainable development.